Influence of trust and conspiracy beliefs on the disclosure of personal data online - Zimaitis, Ignas; Urbonavičius, Sigitas; Degutis, Mindaugas; Kaduškevičiūtė, Vaida (Journal of Business Economics and Management, 2022)
The issue of trust-based personal data disclosure online remains of high importance both in social networking and online purchasing. Additionally, social networking is linked with a controversial factor of conspiracy beliefs that recently received attention because of Covid-19 pandemic. Conspiracy beliefs trigger activities online, but generate hesitations in regards to rational ideas, requests and procedures. Therefore, it is unclear how they impact rational requests of data disclosure in online shopping. The paper analyses how trust and conspiracy beliefs impact willingness to disclose personal data in social networking and in online shopping. The modelling based on the social exchange theory conceptualizes these two online activities as reciprocal and negotiated types of exchange. The findings based on structural equation modelling show some similarities between the impacts of trust and conspiracy believes in case of social networking, but disclose their radical differences in regards to willingness to disclose personal data in online purchasing.First published online 28 February 2022